2012
DOI: 10.1080/07900627.2012.665801
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Agricultural Water Conservation: Empirical Analysis and Policy Implications

Abstract: Climate change and recurrent drought in many of the world's dry places continue to inspire the search for economically attractive measures to conserve water. This study analyzes water conservation practices in irrigated agriculture in a sub-basin in North America's Rio Grande. A method is developed to estimate water savings in irrigated agriculture that result from public subsidies to farmers who convert from surface to drip irrigation. The method accounts for economic incentives affecting farmers' choices on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(39 citation statements)
references
References 36 publications
(27 reference statements)
0
32
0
3
Order By: Relevance
“…PMP is a quadratic programming method and does not analytically integrate agronomic concepts such as efficiency or deficit irrigation. Dagnino and Ward (2012) provided another approach to analyse the rebound effect using a farm microeconomic model and budget analysis. They concluded that although subsidies for drip irrigation in North America's Rio Grande increased farm income and reduced the amount of water applied to crops, such subsidies could increase water depletion in the basin.…”
Section: Mathematical Programmingmentioning
confidence: 99%
“…PMP is a quadratic programming method and does not analytically integrate agronomic concepts such as efficiency or deficit irrigation. Dagnino and Ward (2012) provided another approach to analyse the rebound effect using a farm microeconomic model and budget analysis. They concluded that although subsidies for drip irrigation in North America's Rio Grande increased farm income and reduced the amount of water applied to crops, such subsidies could increase water depletion in the basin.…”
Section: Mathematical Programmingmentioning
confidence: 99%
“…Therefore, taking effective measures to relieve the pressure of water resources exploitation and supply in the river basin is imminently needed. As for the aspect of agriculture, each county should make use of water-saving measures or adjust agricultural planting structure properly to lower irrigation water loss rate and improve irrigation efficiency to alleviate the pressure of agricultural water use [35]. For ecological water, we should minimize its occupation but improve the degree of construction land intensity, and transform construction land expansion into exploitation from its own potentialities to guarantee sufficient ecological water supply for maintaining ecological security of river basin.…”
Section: Optimal Water Resource Allocationmentioning
confidence: 99%
“…Furthermore, widespread adoption of deficit irrigation strategies may have agronomic and basin-scale hydrological consequences in terms of the so-called "rebound effect" described by Dagnino and Ward [25], who conclude that water administrators need to guard against increased depletion of the water sources with growing subsidies that reward reduced water applications. A complete review of the evidence regarding this effect can be found in the work of Berbel et al [26].…”
Section: Discussionmentioning
confidence: 99%